1967
DOI: 10.2134/agronj1967.00021962005900010026x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mulching Methods for Erosion Control on Newly Prepared and Seeded Highway Backslopes1

Abstract: Evaluation of several mulching methods used by different highway departments showed that 2 tons of grain straw per acre provided adequate protection to newly prepared and seeded 2½:1 backslopes when subjected to l‐year frequency storms, 1.3 inches of rain in 30 minutes. However, when subjected to a 10‐year frequency storm, 2.7 inches in 60 minutes, two treatments stood out as superior. These were “whisker dams”, called the Florida method, which permitted 41% runoff and 10 tons per acre soil loss; and surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Estimated delivered sediment was less than observed sediment loss, and this reduction was attributed to the trapping of coarse sediments by downslope vegetation. The benefit of vegetation and obstructions in reducing sediment travel distances has been well documented in the literature (Barnett et al, 1967;Grace, 2000Grace, , 2002bSwift, 1985Swift, , 1986.…”
Section: Road Construction and Maintenancementioning
confidence: 89%
See 1 more Smart Citation
“…Estimated delivered sediment was less than observed sediment loss, and this reduction was attributed to the trapping of coarse sediments by downslope vegetation. The benefit of vegetation and obstructions in reducing sediment travel distances has been well documented in the literature (Barnett et al, 1967;Grace, 2000Grace, , 2002bSwift, 1985Swift, , 1986.…”
Section: Road Construction and Maintenancementioning
confidence: 89%
“…The majority of investigations of forest road effects primarily focus on soil erosion. Erosion rate studies have been conducted extensively throughout the southern states (Appelboom et al, 1998;Barnett et al, 1967;Blackburn et al, 1986;Beasley et al, 1986;Granillo, 1982, 1988;Grace, 2000Grace, , 2002aKochenderfer and Helvey, 1987;Swift, 1984aSwift, , 1984bSwift, , 1985Swift et al, 1993). However, few have related observed erosion rates to the quantity of sediment delivered to water systems or water quality.…”
Section: Road Construction and Maintenancementioning
confidence: 99%
“…Reduction of sediment from fiber mats, straw bales, and so on in welldesigned sites can be as high as 80-90% on a mass basis (Barnett et al, 1967;Benik et al, 2003a,b;Grace, 1999;Jennings and Jarrett, 1985). Nonetheless, Minton and Benedict (1999) noted that the turbidity from these best management practices (BMPs) often still range in value from hundreds to even thousands of nephelometric turbidity units (NTUs).…”
Section: Pam For Construction Sites and Other Disturbed Landsmentioning
confidence: 99%
“…Adams [8] found that straw significantly increased the infiltration and movement of excess water in Temple, Texas. Increasing the soil cover with mulch decreased the runoff and soil loss and increased the apparent infiltration [8,9]. Vegetation also played a key role in the interactions between groundwater and surface-water systems, because of its direct and indirect influence on the recharge and the dependence of vegetation communities on groundwater [10].…”
Section: Introductionmentioning
confidence: 99%